Use and traditional knowledge associated with capuli (Prunus serotina) in an interandean area of Ecuador - Tamayo Ortiz, Christian Vicente (2022)
The study identify the main uses and traditional knowledge associated with capuli (Prunus seronita) in Garcia Moreno, Tungurahua, Ecuador.  This tree is mainly valorized for: (i) Seasonal food for family consumption; (ii) Complementary food for small breeding animals; (iii) Ancestral medicine; (iv) Property delimitation with living fences; (iv) Shade to protect harvested grass; and, (v) Distraction for childcare in the countryside. In spite of this specie is very important, it suffers a constant deterioration. The felling of trees and the decrease in consumption of this specie because of the lack of labor for harvest, put at risk this important biological resource. Face at this things, is necessary to replant the specie, generate add value through product transformation and promote research to determine appropriate designs for use as agroforesty sistems component.